(untitled) (New York, NY., 2001)
This is a high school textbook focusing on english writing. The contents are devided into three section Composition, Grammar, usage and mechanics and Resources and skills
Keywords: Language arts ( Secondary ),Composition ( Language arts ),English language; Composition and exercises